Ecological pervious concrete and preparation method thereof

By using modified regenerated coarse aggregate, waste tire rubber particles and cellulose ether in permeable concrete, the problem of insufficient compressive strength and frost resistance of traditional permeable concrete is solved, and a high compressive and frost-resistant permeable concrete is achieved, which is suitable for high load and cold areas.

CN119551950AActive Publication Date: 2025-03-04SHANWEI GUANGTOU CONSTR ENG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411766389.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-04
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The compressive strength and frost resistance of traditional permeable concrete are insufficient, making it difficult to meet the needs of sidewalks with people loaded with parking or areas with cold and large temperature differences in winter.

Method used

Modified regenerated coarse aggregate and waste tire rubber particles, combined with raw materials such as cellulose ether, to improve the compressive strength and frost resistance of concrete through modified structure and synergistic action.

Benefits of technology

It significantly improves the compressive strength and frost resistance of permeable concrete, making it suitable for use needs in high load and cold areas, and is in line with the concept of green ecological.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169054950000041
    Figure BDA0005169054950000041
  • Figure BDA0005169054950000051
    Figure BDA0005169054950000051
  • Figure BDA0005169054950000052
    Figure BDA0005169054950000052
Patent Text Reader

Abstract

The invention relates to the field of concrete, and discloses ecological pervious concrete and a preparation method thereof. The ecological pervious concrete is prepared from the following raw materials in parts by mass: 68-85 parts of cement; 150 to 200 parts of modified recycled coarse aggregate; 260 to 320 parts of natural coarse aggregate; 4-8 parts of waste tire rubber particles; 25 to 32 parts of water; 1-3 parts of a water reducing agent; and 0.5-1 part of cellulose ether. The pervious concrete prepared by the invention has excellent compressive strength and freezing resistance, and is suitable for sidewalks with crowd load and parking or areas with cold winter and large temperature difference.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to an ecological permeable concrete and a preparation method thereof. Background Art

[0002] At present, building sponge cities has become an effective way to achieve sustainable development, and laying permeable sidewalks in municipal roads, communities, and squares can play an effective role. Permeable sidewalks are a new type of environmentally friendly and ecological road that can allow rainwater to quickly penetrate the surface, effectively replenish groundwater, regulate surface problems, and alleviate the heat island effect and urban waterlogging. At the same time, permeable sidewalks can penetrate the ground, making the ground warm in winter and cool in summer, increasing comfort. In addition, due to the large porosity of permeable sidewalks, they can absorb dust and reduce noise.

[0003] The structure of permeable sidewalks includes surface layer, leveling layer, base layer, cushion layer and soil base. Permeable bricks are often used for the surface layer, medium sand and dry hard cement mortar are used for the leveling layer, permeable cement concrete, permeable cement stabilized gravel, permeable graded gravel are used for the base layer, and natural gravel is used for the cushion layer. The base layer mainly bears loads, is permeable and stores water, and permeable concrete is needed.

[0004] Pervious concrete is essentially a building material made by mixing aggregates, cementitious materials, water and additives. It is mainly composed of coarse aggregate, slurry and voids. Its strength is mainly formed by the hardened cementitious materials wrapped on the surface of the aggregates to bond the aggregates. Traditional pervious concrete has a high permeability coefficient, but its porous structure leads to poor compressive strength and frost resistance. When faced with the need for pedestrian walkways with crowd loads and parking or in areas with cold winters and large temperature differences, traditional pervious concrete cannot meet the use requirements. Summary of the invention

[0005] In order to improve the compressive strength and frost resistance of permeable concrete, so as to adapt it to sidewalks with crowds and parking lots or areas with cold winter and large temperature differences, the present application provides an ecological permeable concrete and a preparation method thereof.

[0006] The present application provides an ecological permeable concrete and a preparation method thereof using the following technical solutions: In a first aspect, the present application provides an ecological permeable concrete, which is made of the following raw materials in parts by weight: 68-85 parts of cement; 150-200 parts of modified recycled coarse aggregate; 260-320 parts of natural coarse aggregate; 4-8 parts of waste tire rubber particles; 25-32 parts water; 1-3 parts of water reducing agent; Cellulose ether 0.5-1 part.

[0007] By adopting the above technical solution, no fine aggregate is added, and part of the modified recycled coarse aggregate is selected to replace the natural coarse aggregate. The modified recycled coarse aggregate has a larger porosity and a higher water permeability coefficient, and the strength of the modified structure is improved; the waste tire rubber particles can slow down the development of concrete cracks during the freeze-thaw cycle, effectively improving the frost resistance of permeable concrete; the combination of waste tire rubber and modified recycled coarse aggregate saves energy and conforms to the green ecological concept. Cellulose ether plays a retarding role, so that the modified recycled coarse aggregate will not hydrate and condense immediately, providing a relatively stable reaction environment for the early hydration inside the recycled coarse aggregate, and at the same time, it can improve the degree of combination of aggregate with cement particles and waste tire rubber particles, and improve the degree of hydration cross-linking, which is conducive to the improvement of the compressive strength of permeable concrete. Through the synergy of various components, the permeable concrete has excellent compressive strength and frost resistance, which is suitable for sidewalks with crowd loads and parking or cold winter areas with large temperature differences.

[0008] Optionally, the preparation method of the modified recycled coarse aggregate is: The waste concrete is crushed, cleaned and screened to obtain recycled coarse aggregate; Cement slurry is prepared by using cement, water, PP wood plastic particles and metakaolin, wherein the mass ratio of cement, water, PP wood plastic particles and metakaolin is (80-88):100:(1.8-3):(4-9); Pour the recycled coarse aggregate into cement slurry, ensure that the liquid level is higher than the recycled coarse aggregate, stir and soak for 2-3 hours, take out the recycled coarse aggregate, sieve it and dry it naturally for later use, so as to obtain modified recycled coarse aggregate.

[0009] By adopting the above technical scheme, the recycled coarse aggregate is treated and modified by cement mortar containing PP wood plastic particles and kaolin. The PP wood plastic particles and kaolin enter the gaps of the recycled coarse aggregate together with the cement mortar to fill them, thereby reducing the porosity of the recycled coarse aggregate and the air content in the pores and improving the compressive strength.

[0010] PP wood-plastic particles are made by mixing thermoplastic plastics with plant fibers such as wood powder, rice husks, and bamboo powder, which can support the pores; kaolin, as a mineral admixture, can change the interface transition zone of recycled concrete. Through the synergy of the two and the cross-linking of the gel products of cement hydration, it is beneficial to improve the compressive strength and chloride ion resistance of permeable concrete and reduce the expansion of cracks.

[0011] Optionally, the waste tire rubber particles are sulfonated modified waste tire rubber particles, and the sulfonated modified waste tire rubber particles are prepared by the following steps: Soak the waste tire rubber particles in 1 mol / L sodium hydroxide solution for 22-24 hours, wash with distilled water until neutral, and dry; The dried waste tire rubber particles and hydrogen peroxide are placed in a reactor and oxidized in a constant temperature water bath at 50-53°C. The pH is controlled at 5.0-5.5 with dilute sulfuric acid. After the oxidation is completed, the particles are washed to neutral and dried. The dried waste tire rubber particles are added to a constant temperature saturated sodium sulfite solution at 60-65° C., subjected to sulfonation reaction for 2-2.5 hours, washed to neutrality, and dried to obtain sulfonated modified waste tire rubber particles.

[0012] By adopting the above technical scheme, sodium hydroxide is used to remove impurities such as zinc stearate on the surface of waste tire rubber particles, and then after oxidation and sulfonation processes, hydrophilic groups such as sulfonic acid groups are introduced into the waste tire rubber particles, thereby enhancing the compatibility and bonding strength of the waste tire rubber particles with the cement matrix, thereby improving the compressive strength of the permeable concrete.

[0013] Optionally, the particle size of the waste tire rubber particles is 5-8 mm.

[0014] By adopting the above technical solution, when 5-8 mm waste tire rubber particles are selected, the influence on the water permeability coefficient of the permeable concrete is small, and a relatively large porosity and water permeability coefficient can still be maintained.

[0015] Optionally, silane coupling agent KH-570 is further added to the cement slurry, and the mass ratio of silane coupling agent KH-570 to water in the cement slurry is (0.8-1.5):100.

[0016] By adopting the above technical scheme, the addition of silane coupling agent is beneficial to enhancing the dispersibility of PP wood plastic particles and kaolin in cement slurry, improving the modification effect on recycled coarse aggregate, and improving the stability of modified recycled coarse aggregate.

[0017] Optionally, the natural coarse aggregate is crushed stone with a particle size range of 8-10 mm, and the modified recycled coarse aggregate has a particle size range of 5-10 mm.

[0018] Optionally, the cement is silicate cement with a strength grade not less than 42.5 MPa.

[0019] Optionally, the water reducer is a polycarboxylate water reducer or a naphthalene-based high-efficiency water reducer.

[0020] Optionally, the particle size of the PP wood-plastic particles is 2-4 mm.

[0021] In a second aspect, the present application provides a method for preparing an ecological permeable concrete, which is used for the above-mentioned ecological permeable concrete, comprising the following steps: Add water reducing agent and cellulose ether into water, stir and mix to obtain a mixed solution; Add modified recycled coarse aggregate, natural coarse aggregate, waste tire rubber particles and cement into a mixing kettle in sequence, add the mixed liquid while stirring, and stir to obtain ecological permeable concrete.

[0022] By adopting the above technical scheme, the water reducing agent, cellulose ether and water are first mixed, and then other gel materials and aggregates are added to obtain ecological permeable concrete with high compressive strength and high frost resistance.

[0023] In summary, this application has the following beneficial effects: No fine aggregate is added, and part of the modified recycled coarse aggregate is selected to replace the natural coarse aggregate. The modified recycled coarse aggregate has a larger porosity and a higher water permeability coefficient, and the strength of the modified structure is improved; the waste tire rubber particles can slow down the development of concrete cracks during the freeze-thaw cycle, effectively improving the frost resistance of permeable concrete; the combination of waste tire rubber and modified recycled coarse aggregate saves energy and conforms to the green ecological concept. Cellulose ether plays a retarding role, so that the modified recycled coarse aggregate will not hydrate and condense immediately, providing a relatively stable reaction environment for the early hydration inside the recycled coarse aggregate. At the same time, it can improve the degree of combination of aggregate with cement particles and waste tire rubber particles, and improve the degree of hydration cross-linking, which is conducive to the improvement of the compressive strength of permeable concrete. Through the synergy of various components, the permeable concrete has excellent compressive strength and frost resistance, which is suitable for sidewalks with crowd loads and parking or cold winter areas with large temperature differences. DETAILED DESCRIPTION

[0024] The present application is further described in detail below in conjunction with Examples 1-10 and Comparative Examples 1-3.

[0025] The waste concrete came from a building demolition site; The waste tire rubber particles come from a waste rubber recycling plant, with a particle size of 5-8mm; Cellulose ether was selected from Shanghai Kaiyin Chemical Co., Ltd.; The cement used is PO.42.5 grade silicate cement; Natural coarse aggregate is crushed stone with a particle size range of 8-10mm; The polycarboxylate water reducer was purchased from Wuhan Huaxuan High-tech Co., Ltd., model HX-YZJ01; The naphthalene-based water reducer was purchased from Shandong Xintengyue Chemical Co., Ltd., type xty-042; PP wood plastic particles were purchased from Dongguan Yucheng Plastic Chemical Co., Ltd. with a particle size of 2-4 mm.

[0026] Preparation Example Preparation Example 1 Preparation of modified recycled coarse aggregate The steel bars in the waste concrete are removed, crushed by a jaw crusher, and the broken pieces are placed in an ultrasonic cleaning machine and washed with water for 1 hour, and aggregates with a particle size of 3-7 mm are screened to obtain recycled coarse aggregate; Put 100kg water, 80kg cement, 1.8kg PP wood plastic particles and 4kg metakaolin into a mixing bucket, stir and disperse for 20 minutes to obtain cement slurry; Pour 50 kg of recycled coarse aggregate into cement slurry, ensure that the liquid level is higher than the recycled coarse aggregate, stir and soak for 2 hours, take out the recycled coarse aggregate and sieve it, sieve out the detached solidified mortar, dry it naturally for later use, and obtain modified recycled coarse aggregate.

[0027] The particle size range of the modified recycled coarse aggregate is 5-10mm.

[0028] Preparation Example 2-Preparation Example 4 The preparation of the modified recycled coarse aggregate is different from that of Preparation Example 1 in that the raw material parameters and reaction time are different, as shown in Table 1.

[0029] Table 1 Preparation Example 5 Preparation of modified recycled coarse aggregate The difference between this preparation example and preparation example 1 is that 0.8 kg of silane coupling agent KH-570 is further added to the cement slurry.

[0030] Preparation Example 6 Preparation of modified recycled coarse aggregate The difference between this preparation example and preparation example 1 is that 1.5 kg of silane coupling agent KH-570 is also added to the cement slurry.

[0031] Preparation Example 7 Preparation of sulfonated modified waste tire rubber particles Soak the waste tire rubber particles in 1 mol / L sodium hydroxide solution for 22 hours, wash with distilled water until neutral, and dry; The dried waste tire rubber particles and hydrogen peroxide are placed in a reactor and oxidized in a 50°C constant temperature water bath. The pH is controlled to 5.0 with dilute sulfuric acid. After the oxidation is completed, the particles are washed to neutral and dried. The dried waste tire rubber particles were added into a constant temperature saturated sodium sulfite solution at 60°C, subjected to sulfonation reaction for 2 hours, washed to neutrality, and dried to obtain sulfonated modified waste tire rubber particles.

[0032] Preparation Example 8 Soak the waste tire rubber particles in 1 mol / L sodium hydroxide solution for 24 hours, wash with distilled water until neutral, and dry; The dried waste tire rubber particles and hydrogen peroxide are placed in a reactor and oxidized in a 53°C constant temperature water bath. The pH is controlled to 5.5 with dilute sulfuric acid. After the oxidation is completed, the particles are washed to neutral and dried. The dried waste tire rubber particles were added into a saturated sodium sulfite solution at a constant temperature of 65°C, subjected to sulfonation reaction for 2.5 hours, washed to neutrality, and dried to obtain sulfonated modified waste tire rubber particles. Example

[0033] Example 1 Preparation of ecological permeable concrete Add 0.1 kg of polycarboxylate water reducer and 0.05 kg of cellulose ether into 2.5 kg of water and stir for 1 min to obtain a mixed solution; 15 kg of modified recycled coarse aggregate prepared in Preparation Example 1, 26 kg of natural coarse aggregate, 0.4 kg of waste tire rubber particles and 6.8 kg of cement were added to the stirring tank in sequence, and the mixed liquid was added while stirring. The ecological permeable concrete was prepared by stirring for 6 minutes.

[0034] Example 2-Example 4 The difference between Example 2 to Example 4 and Example 1 is that the raw materials, raw material parameters and reaction time are different, as shown in Table 2.

[0035] Table 2 Example 5 The difference between this embodiment and embodiment 1 is that the modified recycled coarse aggregate in this embodiment is the modified recycled coarse aggregate prepared in preparation example 5.

[0036] Example 6 The difference between this embodiment and embodiment 1 is that the modified recycled coarse aggregate in this embodiment is the modified recycled coarse aggregate prepared in preparation example 6.

[0037] Example 7 The difference between this embodiment and embodiment 1 is that the waste tire rubber particles in this embodiment are the sulfonated modified waste tire rubber particles prepared in preparation example 7.

[0038] Example 8 The difference between this embodiment and embodiment 1 is that the waste tire rubber particles in this embodiment are the sulfonated modified waste tire rubber particles prepared in preparation example 8.

[0039] Example 9 The difference between this embodiment and embodiment 1 is that the modified recycled coarse aggregate in this embodiment is the modified recycled coarse aggregate prepared in preparation example 6; the waste tire rubber particles in this embodiment are the sulfonated modified waste tire rubber particles prepared in preparation example 8.

[0040] Example 10 The difference between this embodiment and embodiment 1 is that the modified recycled coarse aggregate in this embodiment is the modified recycled coarse aggregate prepared in preparation example 5; the waste tire rubber particles in this embodiment are the sulfonated modified waste tire rubber particles prepared in preparation example 7.

[0041] Comparative Example Comparative Example 1 The difference between this comparative example and Example 1 is that in the raw materials of this comparative example, 15 kg of recycled coarse aggregate is used instead of 15 kg of modified recycled coarse aggregate prepared in Preparation Example 1.

[0042] Comparative Example 2 The difference between this comparative example and Example 1 is that 0.4 kg of waste tire rubber particles are not added to the raw materials of this comparative example.

[0043] Comparative Example 3 The difference between this comparative example and Example 1 is that among the raw materials in this comparative example, in the step of preparing the modified recycled coarse aggregate, the cement slurry is prepared by 100 kg of water and 80 kg of cement, and does not contain PP wood-plastic particles and metakaolin.

[0044] Performance testing The ecological permeable concrete prepared in Examples 1-10 and Comparative Examples 1-3 were made into test pieces, and the compressive strength, water permeability coefficient, and freeze-thaw resistance of each test piece were tested, and the test results were recorded in Table 3.

[0045] Compressive strength: tested in accordance with GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete"; Permeability coefficient: tested the permeability coefficient of permeable concrete in accordance with the provisions of GB / T25993-2010 "Permeable Pavement Bricks and Permeable Road Panels"; Freeze-thaw resistance: Tested in accordance with ASTM / C666 "Standard Test Method for Rapid Freeze-Thaw Resistance of Concrete".

[0046] Table 3 According to Table 3, the water permeability coefficient of the ecological permeable concrete prepared in this application is greater than 2mm / s, the compressive strength after curing for 28 days is greater than 20MPa, and the water absorption rate of the modified recycled coarse aggregate is less than 8%, and the effective porosity is greater than 15%, which meets the design standard of permeable cement concrete for permeable sidewalk base. The ecological permeable concrete of this application has high compressive strength and good frost resistance, so it is suitable for sidewalks with crowd loads and parking or areas with cold winter and large temperature differences.

[0047] Compared with Example 1, Example 4-5 is improved with respect to the modified recycled coarse aggregate in the raw material component, and a silane coupling agent KH-570 is added to the modified cement slurry, which promotes the dispersion of PP wood plastic particles and kaolin in the cement slurry, thereby improving the filling performance of PP wood plastic particles and kaolin for recycled coarse aggregate, thereby promoting the improvement of the compressive strength of concrete.

[0048] Compared with Example 1, Examples 6-7 modify the waste tire rubber particles in the raw material components by introducing hydrophilic groups into the waste tire rubber particles through oxidation-sulfonation, thereby enhancing the compatibility and bonding strength with the cement matrix, playing a partial cross-linking filling role, and improving the compressive strength and frost resistance.

[0049] Compared with Example 1, Comparative Example 1 uses unmodified recycled coarse aggregate, which has low compressive strength and high water permeability and cannot bear the load of the sidewalk.

[0050] Compared with Example 1, in Comparative Example 2, no waste ceramic rubber particles were added to the raw material components, and the obtained permeable concrete had poor freeze-thaw resistance and could not meet the use requirements in areas with cold winters and large temperature differences.

[0051] Comparative Example 3 Compared with Example 1, PP wood-plastic particles and metakaolin were not added to the cement slurry modified with recycled coarse aggregate. Pure cement slurry was used, which reduced the filling capacity of the recycled coarse aggregate and resulted in a decrease in the compressive strength of the eco-concrete.

[0052] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An ecological permeable concrete, characterized in that: Made from the following raw materials in parts by weight: 68-85 parts of cement; 150-200 parts of modified recycled coarse aggregate; 260-320 parts of natural coarse aggregate; 4-8 parts of waste tire rubber particles; 25-32 parts water; 1-3 parts of water reducing agent; Cellulose ether 0.5-1 part.

2. The ecological permeable concrete according to claim 1, characterized in that: The preparation method of the modified recycled coarse aggregate is: The waste concrete is crushed, cleaned and screened to obtain recycled coarse aggregate; Cement slurry is prepared by using cement, water, PP wood plastic particles and metakaolin, wherein the mass ratio of cement, water, PP wood plastic particles and metakaolin is (80-88):100:(1.8-3):(4-9); Pour the recycled coarse aggregate into cement slurry, ensure that the liquid level is higher than the recycled coarse aggregate, stir and soak for 2-3 hours, take out the recycled coarse aggregate, sieve it and dry it naturally for later use, so as to obtain modified recycled coarse aggregate.

3. The ecological permeable concrete according to claim 1, characterized in that: The waste tire rubber particles are sulfonated modified waste tire rubber particles, and the sulfonated modified waste tire rubber particles are prepared by the following steps: Soak the waste tire rubber particles in 1 mol / L sodium hydroxide solution for 22-24 hours, wash with distilled water until neutral, and dry; Place the dried waste tire rubber particles and hydrogen peroxide in a reactor and oxidize them in a constant temperature water bath at 50-53°C. Use dilute sulfuric acid to control the pH to 5.0-5.

5. After the oxidation is completed, wash to neutral and dry. The dried waste tire rubber particles are added to a constant temperature saturated sodium sulfite solution at 60-65° C., subjected to sulfonation reaction for 2-2.5 hours, washed to neutrality, and dried to obtain sulfonated modified waste tire rubber particles.

4. The ecological permeable concrete according to claim 1, characterized in that: The particle size of the waste tire rubber particles is 5-8 mm.

5. The ecological permeable concrete according to claim 2, characterized in that: Silane coupling agent KH-570 is also added to the cement slurry, and the mass ratio of silane coupling agent KH-570 to water in the cement slurry is (0.8-1.5):

100.

6. The ecological permeable concrete according to claim 1, characterized in that: The natural coarse aggregate is crushed stone with a particle size range of 8-10 mm, and the modified recycled coarse aggregate has a particle size range of 5-10 mm.

7. The ecological permeable concrete according to claim 1, characterized in that: The cement is silicate cement with a strength grade not less than 42.5 MPa.

8. The ecological permeable concrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer or a naphthalene-based high-efficiency water reducer.

9. The ecological permeable concrete according to claim 1, characterized in that: The particle size of the PP wood-plastic particles is 2-4 mm.

10. A method for preparing ecological permeable concrete, characterized in that: The method for preparing an ecological permeable concrete according to any one of claims 1 to 9 comprises the following steps: Add water reducing agent and cellulose ether into water, stir and mix to obtain a mixed solution; Add modified recycled coarse aggregate, natural coarse aggregate, waste tire rubber particles and cement into a mixing kettle in sequence, add the mixed liquid while stirring, and stir to obtain ecological permeable concrete.

Citation Information

Patent Citations

  • Preparation method for water permeable concrete

    CN103708792A

  • Environment-friendly anti-freezing type concrete and preparation method thereof

    CN110117179A

  • High-strength recycled concrete and preparation method thereof

    CN113354369A

  • High-strength high-water-permeability pavement paving material

    CN113480275A

  • Preparation method of anti-freezing recycled concrete and anti-freezing recycled concrete

    CN114380562A